The Pahlawan Kerja Train Monument Pekanbaru Correlates with Indonesian History Learning Materials In Grade XI In High School - Asyrul Fikri; Isjoni Isjoni; Yovindra Satria Maulana; Arbain Arbain (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2023)
This article aims to correlate historical heritage objects in Pekanbaru, namely The Pahlawan Kerja Train Monument related to Indonesian history learning materials in grade XI high school. The method used in this study is a qualitative method of observing, interviewing, and studying documentation. This research used the analysis technique of the Miles and Huberman model, that is: Data Collection; Data Reduction; Data Display; and Conclusions. The results of this study found the fact that Monumen Kereta Api Pahlawan Kerja was built to honor the victims of the romusha atrocities during the Japanese occupation. The construction of the railroad with the Muaro Sijunjung-Pekanbaru route has claimed the lives of 300,000 people. Some relics can still be seen to this day are locomotives and train carriages along with a train track that still maintains its authenticity. This historical object deserves to be a source of learning because it meets the eight ideal criteria to be achieved in history learning.